Implementation of Interactive Video in Improving the Digital Literacy Abilities of Elementary School Teachers in Garut City District - Hartinah; Nizar Alam Hamdani; Asep Nurjamin (Riviera Publishing, 2026)
The development of digital technology has brought significant changes to the world of education, particularly in the learning process. This study aims to analyze the effectiveness of interactive video implementation in improving the digital literacy skills of elementary school teachers in Garut City District. The study used a quantitative approach with a pre-experimental design method through a one-group pretest–posttest model. The research subjects consisted of 30 elementary school teachers selected by purposive sampling. The research instruments were a digital literacy test and a questionnaire. Data were analyzed using the N-gain test and paired t-test. The results showed a significant increase in teachers' digital literacy skills after the use of interactive videos, with an average pretest score of 62.4 and a posttest score of 82.7. The N-gain value of 0.54 is included in the moderate category. The t-test results showed a significance value <0.05, so there is a significant effect. This study concludes that interactive videos are effective in improving teachers' digital literacy.